2020
DOI: 10.1096/fj.202001136r
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid induces tumor necrosis factor‐alpha to regulate a pro‐inflammatory cytokine network in ovarian cancer

Abstract: Epithelial ovarian carcinoma tissues express high levels of tumor necrosis factor‐alpha (TNF‐α) and other inflammatory cytokines. The underlying mechanism leading to the abnormal TNF‐α expression in ovarian cancer remains poorly understood. In the current study, we demonstrated that lysophosphatidic acid (LPA), a lipid mediator present in ascites of ovarian cancer patients, induced expression of TNF‐α mRNA and release of TNF‐α protein in ovarian cancer cells. LPA also induced expression of interleukin‐1β (IL‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 73 publications
(128 reference statements)
0
15
0
2
Order By: Relevance
“…The level of LPA in plasma and ascites is increased even in the early stages of OC and has been considered a potential diagnostic marker in OC 46 . LPA stimulates the proliferation, migration, and invasion of OC cells through the regulation of several factors, i.e., vascular endothelial growth factor, tumor-necrosis factor α, and CXC chemokine ligand 47 . In the central nervous system, LPA signaling influences numerous processes, including the proliferation of neural precursor cells, neural and glial development, proper cell migration, and cell survival 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The level of LPA in plasma and ascites is increased even in the early stages of OC and has been considered a potential diagnostic marker in OC 46 . LPA stimulates the proliferation, migration, and invasion of OC cells through the regulation of several factors, i.e., vascular endothelial growth factor, tumor-necrosis factor α, and CXC chemokine ligand 47 . In the central nervous system, LPA signaling influences numerous processes, including the proliferation of neural precursor cells, neural and glial development, proper cell migration, and cell survival 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidic acid (LPA), a lipid growth factor highly secreted in the ovarian tumor microenvironment [13], exerts several pro-tumorigenic activities such as (i) reprogramming toward a glycolytic shift that associates with the pheno-conversion of ovarian normal fibroblasts into cancer-associated fibroblasts (CAFs) [14] and with the enhanced proliferation of ovarian cancer cells [15], (ii) upregulating the oncogenic/growth-promoting transcriptome [16,17], (iii) promoting EMT and invasiveness [18,19], (iv) stimulating the secretion of pro-inflammatory and angiogenic factors (such as TNF-α, IL-6, IL-8, VEGF, etc.) [20,21], and (v) promoting therapy resistance either by supporting an immunosuppressive phenotype or by protecting tumor cells from apoptosis [21]. Additionally, it has been reported that LPA inhibits autophagy in prostate cancer cells [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Further, TNF-alpha enhances ATX production in the adjacent adipose tissue 19 . A recent study showed that LPA induces secretion of TNF-alpha in ovarian cancer cells and thus, adjusts an inflammatory network in ovarian cancer 52 . However, to our knowledge, no prior study has revealed an LPA-induced TNF-alpha secretion in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas we observed an enhanced release of TNF-alpha in MDA-MB-468 cells, we found a decreased secretion of TNF-alpha in MDA-MB-231 cells after incubation with LPA. Wang et al established the involvement of LPAR2 in the mediation of TNF-alpha induction and reported a minor or even inhibitory role of LPAR3 in TNF-alpha release in ovarian cancer cell lines 52 . LPA-induced secretion of TNF-alpha in MDA-MB-468 and the corresponding LPAR expression profile of this cell line in the present study support the proposed involvement of LPAR2 in TNF-alpha production.…”
Section: Discussionmentioning
confidence: 99%